How Good at Neurology are you? – Answers. Issue 1 (1st February 2003) - Goldsmith, Paul; Lennox, Graham; Ray, Julian
Abstract : 1. (ii) (iii) (i) (iv) and perhaps (i) (v) Mild allergic reactions to IVIg are common. Anaphylactic reactions are rare and occur mostly in patients with an underlying IgA deficiency. Also, IVIg may occasionally lead to renal damage. Methotrexate causes interstitial fibrosis and should be avoided if there is already interstitial lung disease. Allopurinol inhibits xanthine oxidase, leading to decreased breakdown of azathioprine . Accumulation and eventual myelosuppression results, unless the dose of azathiorpine is appropriately lowered to 25% of usual, with particularly close monitoring. Cyclosporine causes dose-dependent nephrotoxicity, particularly in patients with pre-existing renal failure and hypertension. Cyclophosphamide can cause a severe and potentially fatal haemorrhagic cystitis and so should be avoided if bladder inflammation is already present. Further reading: Chevrel, Goebels & Hohlfeld. (2002) Myositis: diagnosis and management. Practical Neurology, 2, 4–11. The British National Formulary. http://www.bnf.org 2.